Experience with the tissue bank service in years 2014 and 2020 in Turku, Finland - Tikkala, Santtu (My University, 2022)
Purpose of a musculoskeletal tissue bank is to collect, test, store and provide musculoskeletal tissue allografts required in orthopedic procedures. Allografts are harvested from living and cadaver donors under sterile conditions to avoid allograft bacterial contamination. Cadaver musculoskeletal tissue donors are selected among multiorgan donors, and strict exclusion criteria are followed to prevent transmission of infectious diseases. Tissue banking in Turku, Finland began in 1972, and tissue bank service was last time reviewed in 2003. This study aimed to review operation of VSSHP Tyks Orto tissue bank in Turku, Finland between year 2014 and 2020, and to analyze number, types and contamination rate of allografts harvested from cadaver donors. Potential donor relating factors causing allograft bacterial contamination and whether potential musculoskeletal tissue donors were missed among multiorgan donors were also studied. A retrospective review of cadaver musculoskeletal tissue donors utilized in VSSHP Tyks Orto tissue bank during study period was conducted, and data concerning harvested allografts was collected and presented. Total number of 28 cadaver donors were utilized and 636 allografts were harvested between year 2014 and 2020. Allograft bacterial contamination rate was 2.5 %, which is substantially lower when compared to previous international literature, where contamination rate has varied between 10 and 52 %. Longer average treatment time and higher C-reactive protein levels were recorded in donors with positive bacterial cultures, but more research with higher donor volume is required to verify this correlation. We also discovered that some suitable musculoskeletal tissue donors were missed among multiorgan donors.

Luu- ja tukikudospankin tehtävänä on kerätä, testata, säilyttää ja tarjota luu- ja tukikudossiirteitä, joita tarvitaan ortopedisissä toimenpiteissä. Kudossiirteet kerätään eläviltä ja kuolleilta kudosluovuttajilta steriileissä leikkaussaliolosuhteissa siirteiden bakteerikontaminaation välttämiseksi. Kuolleet kudosluovuttajat valitaan teho-osastolla hoidettujen monielinluovuttajien joukosta, ja tiukkoja poissulkukriteerejä noudatetaan tarttuvien tautien siirtymisen estämiseksi. Luu- ja tukikudospankki on toiminut Turussa, Suomessa vuodesta 1972 lähtien, ja viimeinen katsaus sen toiminnasta on vuodelta 2003. Tämän tutkimuksen tarkoituksena oli tehdä katsaus VSSHP Tyks Orto kudospankin toiminnasta Turussa, Suomessa vuosien 2014 ja 2020 välillä, sekä analysoida kuolleilta kudosluovuttajilta kerättyjen kudossiirteiden määrä, tyypit ja bakteerikontaminaatioaste. Lisäksi tutkittiin mahdollisia kudosluovuttajaan liittyviä tekijöitä, jotka aiheuttavat kudossiirrännäisten bakteerikontaminaatiota sekä jääkö potentiaalisia kudosluovuttajia hyödyntämättä monielinluovuttajien joukosta. Retrospektiivinen katsaus suoritettiin vuosien 2014 ja 2020 välillä VSSHP Tyks Orto kudospankissa hyödynnetyistä monikudosluovuttajista. Aineisto monikudosluovuttajilta kerätyistä luu- ja tukikudossiirteistä kerättiin ja esitettiin tutkimuksessa. Tutkimusaineistossa oli 28 monikudosluovuttajaa, joilta kerättiin yhteensä 636 luu- ja tukikudossiirrettä. Kudossiirteiden bakteerikontaminaatioaste oli 2.5 %, mikä on huomattavasti matalampi verrattuna aiempaan kansainväliseen lähdeaineistoon, jossa kontaminaatioaste on vaihdellut 10 ja 52 %:n välillä. Pidempi keskimääräinen hoitoaika ja korkeampia C-reaktiivisen proteiinin tasoja mitattiin kudosluovuttajilla, joilta löytyi positiivisia bakteerinäytteitä, mutta lisää tutkimusta suuremmalla aineistolla tarvitaan tämän havaitun korrelaation osoittamiseksi. Lisäksi havaitsimme, että joitain potentiaalisia kudosluovuttajia jäi hyödyntämättä monielinluovuttajien joukosta.
Keywords: Tissue bank, Musculoskeletal tissue allograft, Tissue donor, Bone transplantation, Bacterial contamination